PRIVATIZATION OF RUSSIA’S ENERGY ASSETS IN THE INTERNATIONAL CONTEXT - Y. V. Borovsky (MGIMO University Press, 2013)
The article deals with privatization in Russia’s energy sector with a special focus on a recent purchase of the private TNK-BP by the state-owned Rosneft. The author analyses the past, present and future privatization deals related to the Russian oil, gas and power generation industry as compared to accumulated international experience. For instance, the article displays the ways the Norwegian, Brazilian, French and British authorities privatized national strategic energy assets. The study presented in the article also aims to find out key advantages and disadvantages of state or private ownership in the Russian and global energy industry. For example, it sheds light on some considerable achievements of the Russian state-controlled companies in oil production amid a widespread belief that more than a decade-long growth in the Russian oil industry is due only to private firms that were created in the 1990s. Additionally, the state-controlled Norwegian oil and gas firm Statoil that shows strong operational and financial results on the Norwegian Continental Shelf and abroad is also in the spotlight of the current study. In line with the mentioned takeover of TNK-BP the author examines outcomes of the reorganization of RAO UES of Russia (the dismantled Russian electric power monopoly) that was seen as a massive privatization of the national power industry. Moreover, the study presents two groups of interests prevailing in the Russian government and energy business to give an outlook on the Russian energy industry.